Transient Spaces: unsettling boundaries and norms at the cultural event Noc Noc, Guimarães, Portugal - Sarmento, João (2014)
Cities are increasingly expected to be creative, inventive and to exhibit intense expressivity. In the past decades many cities have experienced growing pressure to produce and stage cultural events of different sorts and to develop new strategies that optimize competitive advantages, in order to promote themselves and to boost and sell their image. Often these actions have relied on heavy public investment and major private corporation sponsoring, but it is not always clear or measured how successful and reproductive these investments have been. In the context of strained public finances and profound economic crisis of European peripheral countries, events that emerge from local communities and have low budgets, which manage to create significant fluxes of visitors and visibility, assume an increased interest. In order to reflect and sketch possible answers, we look to an emerging body of literature concerning creative cities, and we focus on the organisation of a particular cultural event and its impact and assimilation into a medium size Portuguese city. This paper looks at the two editions (2011 and 2012) of one of such events – Noc Noc – organized by a local association in the city of Guimarães, Portugal. Inspired by similar events, Noc Noc is based on creating transient spaces of culture which are explored by artists and audiences, by transforming numerous homes into ephemeral convivial and playful social ‘public’ environments. The event is based on a number of cultural venues/homes scattered around the old and newer city, which allows for an informal urban exploration and an autonomous rambling and getting lost along streets. This strategy not only disrupts the cleavages between public and private space permitting for various transgressions, but it also disorders normative urban experiences and unsettles the dominant role of the city council as the culture patron of the large majority of events. Guimarães, an UNESCO World Heritage City was the European Capital of Culture in 2012, with a public investment of roughly 73 million euro. By interviewing a sample of people who have hosted these transitory art performances and exhibitions, sometimes doubling as artists, the events’ organizers and by experience both editions of the event, this paper illustrates how urban citizens’ engagement and motivations in a low budget cultural event can strengthen community ties. Furthermore, it also questions the advantages of large scale high budget events, and how this event may be seen as unconscious counter movement against a commodification of cultural events and everyday urban experience at large, engaging with the concepts of staging and authenticity.